Corporate Finance Practices and Digitalization in the Gulf Cooperation Council Countries: Challenges, Opportunities, and Future Directions - Khan, Mohammed Abdul Imran; Ali, Meer Mazhar; Khan, Shahebaz Sarfaraz (Current Topics on Business, Economics and Finance Vol. 6, 2023)
This chapter provides an overview of corporate finance practices in the Gulf Cooperation Council (GCC) countries. The chapter reviews recent literature on the topic and discusses the importance of corporate finance in the economic development of the region. It also examines the challenges faced by firms in the GCC countries and the ways in which they have adapted to the changing business environment. Corporate finance and digitalization have become two inseparable concepts in today's business landscape. As digital technology continues to evolve, it has become increasingly clear that companies that embrace digitalization in their finance functions can achieve greater efficiency, accuracy, and cost savings. This chapter will also explore some of the ways digitalization is transforming corporate finance. The chapter concludes with a discussion of the future of corporate finance in the GCC countries and the need for continued research in the field.